FACTORS THAT HAVE PROGNOSTIC VALUES IN THE MANAGEMENT OF NASOPHARYNGEAL CARCINOMA PATIENTS - Chandra Kangga; Denny Satria Utama (INTERNATIONAL JOURNAL OF NASOPHARYNGEAL CARCINOMA, 2020)
Introduction: The survival rate of Nasopharyngeal carcinoma (NPC) patients is influenced by several prognostic factors, Such aspatient factors, tumor factors and therapeutic interventions carried out as well as the quality of care. Tumor factors in the form of spread of local invasion, regional lymphatic involvementand metastasis that is reflected in the TNM stage (Tumor, Nodule and Metastatic) are the most important prognostic factors of NPC. Objective: To determine the Prognostic factors that effectedsurvival rate of nasopharyngeal carcinoma patients. Material and methods: Analytic observational studywith particular design of survival analysis. Data was taken from medical records and then performed survival analysis on the studiedfactors. Sample of this studywas all patients who were first diagnosed NPC From January 2013 until December 2013 and meetinclusion and exclusion criteria is52 patients. Results:From 52 patients in the fifth year, 50% died and 50% survive. Survival was worse in the 30-39 year age group (30.8%), male sex (47.2%), Stage IV (44.4%), T4 size (40%), N1 size (23,1%), Distant metastases (40%), WHO type III (48.5%), chemoradiation (48.9%). In multivariate analysis, it was found that the variables that most influenced the survival of NPC patients based on p <0.05 and based on hazard ratio strength were T-size, N-size categories and Metastasis with 95% CI. Conclusion: Prognostic factors that affect the survival of NPC patients in RSUP. Dr. Mohammad Hoesin Palembang is a category of size T, N, and Metastasis.